The Effect of Combined Therapy with a Proton Pump Inhibitor and Rebamipide on the Clinical Course and Morphofunctional Changes of the Esophageal Mucosa in Patients with Non-Erosive Reflux Disease - A. A. Makushina; A. S. Trukhmanov; A. B. Ponomarev; O. A. Storonova; A. V. Paraskevova; P. G. Ermishina; V. A. Mironova; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2025)
Aim: to evaluate the effect of combined therapy with a proton pump inhibitor and rebamipide on clinical manifestations and morphofunctional changes in the esophageal mucosa in patients with non-erosive reflux disease.Materials and methods. The study included 39 patients with non-erosive reflux disease randomized into the main group (omeprazole 20 mg/day + rebamipide 300 mg/day) and the comparison group (omeprazole 20 mg/day). The duration of treatment was 4 weeks. Histological examination of esophageal mucosa biopsies (hematoxylin-eosin staining), morphometry of intercellular spaces, and immunohistochemical assessment of tight junction protein expression (claudin-1, -4, occludin) were performed. Symptoms were evaluated using the Likert scale.Results. The combined therapy group showed significant reductions in heartburn severity (p < 0.001) and belching (p = 0.004), with absent/mild symptoms in 63.7 and 72.4 % of patients, respectively. In the proton pump inhibitor monotherapy group, 53 % of patients retained moderate or severe heartburn. Morphologically, the combined group demonstrated reduced eosinophilic infiltration (p = 0.030). Occludin expression increased in both groups but reached statistical significance only in the monotherapy group (p = 0.046).Conclusion. The combined therapy with proton pump inhibitor and rebamipide improves symptoms and morphological outcomes in non-erosive reflux disease. Increased occludin expression suggests restored integrity of intercellular junctions. Further studies with larger cohorts and extended follow-up are needed to confirm these findings.